(untitled) (Revista de Física Médica, 2015)
In this work the process for the detection and/or removal of the sentinel lymph node and nonpalpable lesions has been optimized. For the latter, a I-125, seed an isotope that is not usually used for this purpose, is employed. It was recycled from radiotherapy treatments surpluses, having requested the necessary authorizations. A detailed procedure for the management, storage, transport and sterilization of the I-125 seed in the hospital has been developed. A custom protocol has been defined for quality control of intraoperative probes with different tests, providing methods, frequencies, tolerances, etc. The overall result is an improvement of the process and a decrease of the inconveniences for the patient.